Start-up A Practical Guide to Starting and Running a New Business - Harris, Tom. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
So your dream is to start your own business. But how do you know if it will work and how do you make it a reality? Start-up is a user guide for aspiring entrepreneurs and provides expert advice and guidance on every aspect of launching a new business. It will be of particular value if you are an academic wishing to exploit the commercial value of a new technology or business solution through the creation of a new company. Step-by-step, this inspiring and highly readable book covers how to evaluate the strength of your business idea, how to protect your invention, what legal steps and responsibilities are involved in forming a company, how to position your products in the market, how to create a business plan and raise finance. The case studies, practical exercises and tips in this book will help to demystify the process of starting a new business, give you the confidence to do it and greatly increase your chances of realising your dream.